Nanocarriers in Gene Therapy: Bridging Nanotechnology and Diseases (Jagannath University Journal of Science, 2025)
Nanoparticles have emerged as transformative tools in gene therapy, presenting innovative solutions to address the challenges of gene delivery. These minuscule particles (between 1 and 100 nm), often, can be engineered to carry and to protect genetic material such as DNA or RNA with ensuring its stability and functionality until it reaches the target cells. The identical and physicochemical properties of nanoparticles, including their surface charge, size and shape, facilitate their penetration through biological barriers and enhance cellular uptake. One of the significant advantages of using nanocarriers for gene delivery is their capacity to be tailored for specific applications. By modifying the surface of nanoparticles with ligands, peptides, or antibodies, they can achieve targeted delivery to particular cell types, thus increases the precision of gene therapy and minimizes off-target effects. These nanoparticles can be designed to release their genetic payload in response to particular stimuli such as enzymatic activity or pH changes, providing controlled and sustained gene expression. Nanoparticles offer a promising platform for gene delivery, holding the potential to treat a myriad of genetic disorders with precision and efficacy.Jagannath University Journal of Science, Volume 11, Number 2, Dec. 2024, pp. 99−107